2018
DOI: 10.1038/s41586-018-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst-like structures generated solely from stem cells

Abstract: The blastocyst (the early mammalian embryo) forms all embryonic and extra-embryonic tissues, including the placenta. It consists of a spherical thin-walled layer, known as the trophectoderm, that surrounds a fluid-filled cavity sheltering the embryonic cells . From mouse blastocysts, it is possible to derive both trophoblast and embryonic stem-cell lines , which are in vitro analogues of the trophectoderm and embryonic compartments, respectively. Here we report that trophoblast and embryonic stem cells coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
375
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(413 citation statements)
references
References 46 publications
(59 reference statements)
8
375
1
2
Order By: Relevance
“…The formation of embryoid bodies can be divided into four stages: blastocyst, early post‐implantation, gastrulation and post‐gastrulation. Blastocyst formation reveals that ES maintains TS proliferation and self‐renewal during embryogenesis and regulates trophoblast epithelial morphogenesis through BMP4/Nodal‐KLF6 . Early post‐implantation illustrates the role of Nodal signalling during ETS‐embryogenesis .…”
Section: Main Strategies Of the Embryonic Developmentmentioning
confidence: 99%
“…The formation of embryoid bodies can be divided into four stages: blastocyst, early post‐implantation, gastrulation and post‐gastrulation. Blastocyst formation reveals that ES maintains TS proliferation and self‐renewal during embryogenesis and regulates trophoblast epithelial morphogenesis through BMP4/Nodal‐KLF6 . Early post‐implantation illustrates the role of Nodal signalling during ETS‐embryogenesis .…”
Section: Main Strategies Of the Embryonic Developmentmentioning
confidence: 99%
“…It is exciting that recent advances in three-dimensional organoid culture techniques have led to the generation of primitive "organs" from ESC-differentiated cells. 129,130 This model could be extended to investigate innate immunity development at the blastocyst stage. 129,130 This model could be extended to investigate innate immunity development at the blastocyst stage.…”
Section: The Reduced S En S Itivit Y Of E Sc S To Emb Ryotoxi C C Ymentioning
confidence: 99%
“…128 It is now feasible to reconstitute a blastocyst-like structure with ESCs and TSC-derived trophoblasts that can recapitulate certain developmental events of early embryogenesis. 129,130 This model could be extended to investigate innate immunity development at the blastocyst stage. With the knowledge and resources that have been obtained from stem cell research, the emergence of new tissue culture models and molecular tools, such as gene editing, will provide more exciting interdisciplinary opportunities for a deeper understanding of early embryogenesis, immunology, and reproductive biology, which is otherwise difficult or impossible with in vivo studies.…”
Section: The Reduced S En S Itivit Y Of E Sc S To Emb Ryotoxi C C Ymentioning
confidence: 99%
“…Recent studies have reported methods to generate blastocyst-like structures for experimental mouse models 3,4 . However, these studies used and digested blastocysts from fertilized eggs to obtain embryonic stem cells (ESCs) 5 and trophoblast stem cells (TSCs).…”
Section: Mainmentioning
confidence: 99%